PERANCANGAN ALAT UKUR KELEMBABAN TANAH MENGGUNAKAN CAPACITIVE SOIL MOISTURE SENSOR BERBASIS ANDROID - Komang Tri Jaya Maghuna; I Made Satriya Wibawa; Putu Suardana; I. G. A Widagda; Ni Luh Putu Trisnawati; I Gde Antha Kasmawan (Kappa Journal, 2024)
A soil moisture measuring instrument has been designed and created using an Android-based capacitive soil moisture sensor. The design of a soil moisture measuring instrument was made to understand how to design, how it works, and the results of calibration. The process of calibrating and applying the design tool is carried out by comparing the results of soil moisture measurements between the design tool and the reference tool. The calibration itself was carried out using black sand soil into which 0 ml, 10 ml, 30 ml, 50 ml and 70 ml of water were poured periodically. The reference tool used is the soil moisture meter pH tester VT05 with type ZD-05. Data collection is carried out by inserting a capacitive soil moisture sensor into the soil. There are five types of soil used during application, namely white sand soil, black sand soil, limestone soil, clay soil and humus soil. The results of calibration using linear regression between the design tool and the reference tool obtained a gradient value m of 0.9643, close to 1. The coefficient of determination value obtained during calibration was 0.9983, so the level oflinearity between the design tool and the reference tool was 99.83%. The results of applying linear regression between the design tool and the reference tool obtained a gradient value m of 1.0041, close to 1. The coefficient of determination () obtained when applying was 0.9982, so the level of linearity between the design tool and the reference tool was 99.82%. From the results of the calibration and application of the tool, it shows that the tool design has good validity (precise accuracy).